The indirect economic effects of Ecopetrol's contracting strategy for informatics development. - Garcia, Alberto
This paper is an attempt to identify and quantify the indirect economic effects generated by the informatics contracting strategy of the public Colombian petroleum company (Ecopetrol), the most important public company as source of public funds in Columbia. The methodology used for this purpose was an adaptation of an original one designed by the European Space Agency, to measure the spin-offs generated by its technological development contracting strategy. The conclusions of the study are based on personal interviews of the main 18 Ecopetrol's informatics suppliers. The research found that the informatics suppliers could be grouped into four main categories according to the economic effects generated by them, and to the kind of business relationships with Ecopetrol. This classification not only helps Ecopetrol to understand the kind of contracts that best fit each kind of supplier, but also shows how to plan the long term technological development of their suppliers. The final result indicates that on average, each dollar contracted by the Ecopetrol's Informatics Division generates a further 3.6 US dollars in value added to the Colombian economy through new sales, new contracts and cost reductions. An important effect, due to the effects, is generated in information technology firms, which compose a strategic business sector for the future of the country. Final comparisons of these results against those of other international research projects are also presented.
The paper is based on the conclusions from eighteen interviews with the Informatics Suppliers of Ecopetrol, a Colombian Petroleum Company, with the aim of identifying and quantifying the economic effects generated by the Informatics Contracting Strategy.